Inhibition of Histone Deacetylase 6 Reveals a Potent Immunosuppressant Effect in Models of Transplantation. Issue 8 (August 2016) - Ellis, Jonathan D.; Neil, Desley A.H.; Inston, Nick G.; Jenkinson, Eric; Drayson, Mark T.; Hampson, Peter; Shuttleworth, Stephen J.; Ready, Andrew R.; Cobbold, Mark
Abstract: Background: Current transplant immunosuppression regimens have numerous limitations. Recent evidence suggests histone deacetylase inhibitors (HDACis) may represent a class of drug with immunosuppressive properties. This study compares cyclosporin A (CyA) with the pan-HDACi suberoylanilide hydroxamic acid (SAHA) and a novel HDAC6-specific inhibitor (KA1010) in models of alloreactivity. Methods: Proliferation and mixed lymphocyte reaction (MLR)-based assays were used to determine the immunosuppressive effect of compounds, and a murine model of allogeneic skin transplantation was adopted to assess the in vivo effects of HDAC6 inhibition. Results: KA1010 displayed superior inhibitory effects on the activation of peripheral mononuclear cells using in vitro models of transplantation. In a 1-way MLR, KA1010 (5 μΜ) reduced parent cell proliferation from 92% to 64% ( P = 0.001). A 2-way MLR, adopting IFN-γ production as a marker of alloresponse, resulting in up to 91% reduction. Dose-response curves revealed dose-dependent profiles with greater potency of HDACis over CyA (IC50 values of 82.0 nM and 13.4 nM for KA1010 and SAHA). Mice treated with KA1010 displayed no significant features of skin allograft rejection upon histological analysis at 70 days and graft survival of 80% in subjects treated with 160 mg/kg. Immunological assessment, revealed a significant increase in CD4 + CD25 + forkhead box P3 + regulatory T cells (from 18% to 25%, P = 0.0002) and a corresponding reduction in CD4 + T cells (from 58% to 42%, P = 0.0009). Conclusions: HDAC6 may represent an optimal target for future immunosuppressant therapeutics with a particular role in transplantation. In this article, we have demonstrated a superior immunosuppressive effect of KA1010 over both CyA and SAHA, in the models of allotransplantation adopted. Abstract : This study demonstrates that a novel histone deacetylase (HDAC) 6-specific inhibitor (KA1010) has superior immunosuppressive activity over cyclosporine and a pan-HDACi inhibitor, suberoylanilide hydroxamic acid, using in vitro MLR assays and in vivo, using an experimental skin transplant model.